A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group - Longino, John T. (Zootaxa, 2007)
The genus Azteca is endemic to the American tropics, where they are abundant arboreal ants. The taxonomy and natural history of the Costa Rican fauna is reviewed, and the A. aurita group is recognized and revised globally. The following synonymies are proposed: A. laticeps Forel under A. chartifex Forel; A. championi Forel, A. eiseni Pergande, A. raptrix Forel, A. ursina Forel, and A. xysticola Forel under A. forelii Emery; A. rossi and A. surubrensis Forel under A. gnava Forel; A. major Forel under A. instabilis (F. Smith); A. prorsa Wheeler under A. longiceps Emery; A. patruelis Forel under A. pittieri Forel; A. nigriventris Forel and A. rectinota Forel under A. velox Forel; A. silvae Forel under A. aurita Emery; A. pruinosa Mann under A. lallemandi Forel; A. lacrymosa Forel under A. pilosula Forel; A. fiebrigi Forel, A. clariceps Santschi, and A. pallida Stitz under A. schimperi Emery; A. columbica Forel under A. jelskii Emery; A. mexicana Emery under A. sericea (Mayr). Azteca velox nigra Forel is raised to species. Azteca aurita pilosula is removed from synonymy and raised to species. The following new species are described: A. sericeasur, A. flavigaster, A. oecocordia, A. nanogyna, and A. quadraticeps.